Individuals with filaggrin‐related eczema and asthma have increased long‐term medication and hospital admission costs3. (31st May 2018) - Soares, P.; Fidler, K.; Felton, J.; Tavendale, R.; Hövels, A.; Bremner, S.A.; Palmer, C.N.A.; Mukhopadhyay, S.
Summary: Background: Eczema and asthma are chronic diseases with onset usually before the age of 5 years. More than 50% of individuals with eczema will develop asthma and/or other allergic diseases. Several loss‐of‐function mutations in filaggrin (FLG) have been identified in patients with eczema. However, the association of FLG with healthcare use is unknown. Objectives: To determine whether FLG mutations are associated with increased prescribing for eczema and asthma and whether increased prescribing is associated with increased healthcare costs. Methods: A secondary analysis of BREATHE, a cross‐sectional study of gene–environment associations with asthma severity, was undertaken. BREATHE data was collected for 1100 participants with asthma, in Tayside and Fife, Scotland during the period 2003–2005. Through collaboration with the Health Informatics Centre in Dundee, BREATHE was linked to accident and emergency, community prescribing and Scottish morbidity records. The data linkage allowed longitudinal exploration of associations between genetic variation and prescribing. Results: An association was found between FLG mutations and increased prescribing for mild and moderate eczema, asthma‐reliever medicine and asthma exacerbations. A strong association was found between FLG mutations and prescribing of emollients [incidence rate ratio (IRR) 2·19, 95% confidence interval (CI) 1·36–3·52], treatment for severe eczema (IRR 2·18, 95% CI 1·22–3·91) and a combination of a long‐acting β2 ‐agonist and corticosteroids (IRR 3·29, 95% CI 1·68–6·43). Conclusions: The presence of FLG mutations in this cohort is associated with increased prescribing for eczema and asthma. Randomized controlled trials are required to determine if these individuals could benefit from management strategies to reduce morbidity and treatment costs. Abstract : What's already known about this topic? Defects in FLG are associated with the development of eczema in children. Defects in FLG are associated with severe and persistent eczema and severe asthma. What does this study add? Patients with FLG mutations were dispensed more prescriptions for both eczema and asthma and had more asthma exacerbations over a 9‐year period of study. This translates into higher long‐term costs for these patients. Children and adults with FLG mutations may benefit from targeted treatment regimens that could reduce morbidity and treatment costs in this subgroup. Linked Comment: Akiyama and Bray. Br J Dermatol 2018;179 :564–565 . Plain language summary available online Respond to this article